Mechanical properties of chitin polymorphs: A computational study - Wei, Anran; Fu, Jimin; Guo, Fenglin (Journal of materials science, 2021)
Chitin-based bio-composites in nature such as the exoskeleton of crustaceans and squid pen usually exhibit hierarchical structures, where the chitin crystal is the most fundamental structural hierarchy as the load-bearing scaffold. Previous studies have unveiled the mechanical design of the structures at high hierarchies in these biomaterials, while the structure–property relationship remains unclear for the chitin crystal at the bottom hierarchy. In this paper, we investigate the mechanical properties of chitin crystals with α - and β -polymorphic structures that mainly exist over the animal kingdom using the reactive force field molecular dynamics simulations. We first validate the force field parameters adopted from literature then study the mechanical behaviors of chitin polymorphs in response to the tensile and shear deformation. It is found that the mechanical performance of α -chitin crystal is comprehensively superior to that of β -chitin crystal, such as the elastic modulus, work of fracture, shear modulus and strength. Different from the β -chitin, yielding caused by the transformation of crystalline structure is observed in the α -chitin during uniaxial tension. Based on the mechanical properties obtained from simulations and theoretical analysis, we can deduce that the α -chitin shows higher wear resistance than the β -chitin, implying better protection against the surface scratch that is one of the environmental threats to organisms. Our results shed light on the structure–property relationship of chitin crystals at the molecular level. The fundamental understanding of mechanical properties of chitin polymorphs is of great significance for the bottom-up modeling and design of chitin-based bio-composites. Graphical abstract